Gennaro's cucina : hearty money-saving meals from an Italian kitchen - Contaldo, Gennaro (Interlink Books, an imprint of Interlink Publishing Group, Inc., 2023)
"Join Gennaro Contaldo on a journey of rediscovery to find regional staples that will revolutionize the way you cook. Gennaro's Cucina showcases the very best of "cucina povera," the food that traditionally fed the poor of Italy. It's a simple philosophy-delicious, hearty meals using accessible and affordable ingredients"--